2019
DOI: 10.1037/ser0000191
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as an intervention for psychological symptoms following trauma: A systematic review and quantitative synthesis.

Abstract: Despite evidence of the physiologic impact of trauma, treatments are only beginning to focus on the impact of trauma on the body. Yoga may be a promising treatment for trauma sequelae, given research that supports yoga for general distress. The present study aims to systematically assess and quantitatively synthesize the effectiveness of yoga interventions for psychological symptoms (posttraumatic stress disorder [PTSD], depression, anxiety symptoms) following potentially traumatic life events. The following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 58 publications
(224 reference statements)
0
31
0
Order By: Relevance
“…However, changes in negative posttrauma cognitions may only be one of the important mechanisms. Recent research has suggested that yoga and mindfulness interventions may have some benefits for individuals with PTSD (Davis et al, 2019 ; Nguyen-Feng, Clark, & Butler, 2019 ). Thus, future studies examining intensive PTSD treatments that combine evidence-based PTSD treatments with integrative interventions (e.g., mindfulness and yoga) should also evaluate the mechanisms by which these interventions may contribute to initial symptom reduction and longer-term maintenance of treatment gains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, changes in negative posttrauma cognitions may only be one of the important mechanisms. Recent research has suggested that yoga and mindfulness interventions may have some benefits for individuals with PTSD (Davis et al, 2019 ; Nguyen-Feng, Clark, & Butler, 2019 ). Thus, future studies examining intensive PTSD treatments that combine evidence-based PTSD treatments with integrative interventions (e.g., mindfulness and yoga) should also evaluate the mechanisms by which these interventions may contribute to initial symptom reduction and longer-term maintenance of treatment gains.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, given the design of the clinical programme, we were unable to determine which of the interventions offered during the ITP contributed the most to treatment success. Although CPT is considered a core component of the ITP, recent research has shown that mindfulness and yoga practice can also significantly contribute to PTSD symptom reductions (Davis et al, 2019 ; Nguyen-Feng et al, 2019 ). Thus, any findings need to be attributed to the ITP in general rather than any of the specific programme components.…”
Section: Discussionmentioning
confidence: 99%
“…An a priori power analysis for analysis of variance (repeated measures, within-between interaction) was conducted. Based on previous meditation-based interventions for posttraumatic stress [ 32 , 34 - 36 , 73 ], we expected a small to medium effect size of d =0.30 and a repeated measures correlation of 0.60. To achieve a statistical power of at least .80, a sample size of 72 participants was required.…”
Section: Methodsmentioning
confidence: 99%
“…Not only can feelings of stress be reduced and emotion-regulation capacities improved, individuals also showed beneficial changes in cardiovascular activity [ 29 - 31 ]. Meditation can restore activity and connectivity in brain regions associated with posttraumatic symptoms [ 32 ], lead to more balanced patterns of neurobiological stress responses [ 33 ], and modulate both hypothalamic-pituitary-adrenal axis and autonomic nervous system reactivity [ 34 ]. Research on the effectiveness of meditation interventions for posttraumatic stress shows encouraging findings.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recent systematic reviews on the effect of yoga and meditation as an adjunct therapy have shown promising effects on reducing stress, 11 hypertension, 12,13 post-traumatic stress disorder, anxiety and depression. 14 To date, there has been no systematic review of the literature on the effect of yoga and meditation on tinnitus. Thus, the present systematic review was planned to explore the published literature on the application of yoga and meditation on tinnitus.…”
Section: Introductionmentioning
confidence: 99%